2014
DOI: 10.1111/bjh.12757
|View full text |Cite
|
Sign up to set email alerts
|

The role of apoptosis in megakaryocytes and platelets

Abstract: SummaryThe role of apoptotic pathways in the development and function of the megakaryocyte lineage has generated renewed interest in recent years. This has been driven by the advent of BH3 mimetic drugs that target BCL2 family proteins to induce apoptosis in tumour cells: agents such as ABT-263 (navitoclax, which targets BCL2, BCL-X L [BCL2L1] and BCL2L2) and ABT-199 (a BCL2-specific agent) are showing great promise in early stage clinical trials. However, the major dose-limiting toxicity of navitoclax has pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
82
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(85 citation statements)
references
References 96 publications
2
82
0
1
Order By: Relevance
“…Apoptosis in platelet generation has been previously studied; the reader is referred to an excellent review covering the historical perspective of this topic. 28 A renewed interest in the role of the apoptotic pathway in megakaryopoiesis and platelet generation came with the success of BH3 mimetics that target the intrinsic apoptotic pathway and are used as antitumor drugs for the treatment of cancer. One drug in particular, ABT-737 29 or navitoclax, 30 induced thrombocytopenia in patients due to the off-target inhibition of the prosurvival protein Bcl-xL.…”
Section: Overcoming the Challenges Megakaryocyte In Vitro Injuriesmentioning
confidence: 99%
“…Apoptosis in platelet generation has been previously studied; the reader is referred to an excellent review covering the historical perspective of this topic. 28 A renewed interest in the role of the apoptotic pathway in megakaryopoiesis and platelet generation came with the success of BH3 mimetics that target the intrinsic apoptotic pathway and are used as antitumor drugs for the treatment of cancer. One drug in particular, ABT-737 29 or navitoclax, 30 induced thrombocytopenia in patients due to the off-target inhibition of the prosurvival protein Bcl-xL.…”
Section: Overcoming the Challenges Megakaryocyte In Vitro Injuriesmentioning
confidence: 99%
“…They act either by binding/antagonizing the antiapoptotic BCL-2 family members or by direct binding and activation of the proapoptotic multi-BH domain BCL-2 family members BAX/BAK (14). It has been reported that different antiapoptotic BCL-2 family members are critical for the survival of distinct immune cell subsets: e.g., BCL-2 for naïve B cells (15), BCL-XL for erythroid progenitors and platelets (16), and MCL-1 for germinal center B cells and plasma cells (17,18). It would therefore seem worthwhile to determine which antiapoptotic proteins maintain the survival of the different DC subsets.…”
mentioning
confidence: 99%
“…Over the last 15 years, a body of evidence has emerged to suggest that megakaryocytes deliberately undergo apoptosis in order to promote proplatelet formation and platelet shedding 3 . There are two distinct, convergent, pathways to apoptosis in mammals-the intrinsic and extrinsic-and both have been implicated in thrombopoiesis 4 .…”
mentioning
confidence: 99%